Basic Facilities in Secondary Level Schools in Rural India - Singh, Virendra Pratap; Sharma, Sandeep Kumar (JOURNAL OF INDIAN EDUCATION, 2009)
This paper specifically deals with the need of basic infrastructural facilities and non-availability thereof in secondary level schools in rural area based on the secondary sources of data of fifth, sixth and seventh educational (census) surveys conducted in India. The selected parameters of basic infrastructural facilities in this paper are number of rural habitations not having access to secondary and higher secondary schooling facilities. In addition, management-wise data analysis on rural secondary level schools (covering secondary and higher secondary schools) in the study include number of schools; having Kutcha buildings; non-availability of drinking water facility, non-availability of urinal facility; non-availability of lavatory facility; number of sections not having usable blackboards; number of sections having inadequate and not having mats/furniture for students; and nonavailability of playground facility. The paper reveals about the condition of these selected parameters of basic infrastructural facilities, and provides some directions with regard to areas of concern required for quality learning and physical environment in schools, and may certainly be considered to take up by the public authorities in coming decades to improve the quality of education in secondary level schools existing in Rural India.